Mentalization in psychology college students (Revista de Psicología, 2021)
Mentalization isconsidered as an enriching and useful clinical competence in the training of psychologists, especially clinical ones. The objective was to analyze the mentalization capacity in psychology students and to identify if there were significant differences according to in which year of study they are in —first, third and fifth year. The sample consisted of 169 university students who responded to the instruments: Mentalization Scale (Ments) and Mentalization Questionnaire (MZQ). The results of the study showed significant differences according to the degree of advancement of the career in two dimensions of mentalization, psychic equivalence and the regulation of affect. That is, it is observed that the students who are more advanced in the career obtained better levels of mentalization, in 2 of the 7 evaluated dimensions of mentalization, although the results must be considered in relation to the limitations of the scales. Conclusions: It is worth emphasizing that the results in relation to the other dimension did not obtain significant differences throughout the career. Given that psychotherapeutic treatment and its effectiveness are linked to the quality of relationships with the other, it is important to consider the possibility of its development during university training and at the beginning of the profession. The present study represents a significant contribution, since it allows raising the possibility of training in mentalization as part of undergraduate training in psychology
Keywords: mentalization; college students; training; psychology